The legacy of China (Clarendon Press, 1964)
As China's international status grows, its civilization excites an increasing interest from the outside world. The Legacy of China is the perfect solution for anyone in need of a non-textbook introduction to the world's legacies from China in the major realms of spirit and intellect. This highly-praised work includes essays by eminent experts like Joseph Needham, A. C. Graham, Michael Sullivan and Patrick Hanan on science, philosophy, art and literature.